PRELIMINARY STUDY RESULTS ON FEATURES OF THE OFFICERS’ EMOTIONAL INTELLIGENCE - Baghdasaryan , S. M. (Modern Psychology, 2021)
Military Service is a special type of activity, which is associated with risks, emergent situations, performing complex professional tasks, emotional restraints. Given these conditions, servicemen ought to have a proper level of education, physical and psychological readiness. Within the mentioned factors, emotional intelligence as emotional stability aspect becomes of high value, because it assists commanders and chiefs in making prompt and appropriate decisions also in preventing conflicts during daily routine, maintaining calmness and judgment. Therefore, the development of emotional intelligence becomes a priority in the military domain. The article presents the preliminary study results of the officers’ emotional intelligence, which are presented according to the age. Officers have a low level of self-control and self-motivation skills, they have difficulty in controlling their emotions as well as their own behavior.
Keywords: Military Service; Officers; emotional intelligence; emotional restraint; self-motivation